Assessment of West Kalimantan's border dynamics: Challenges in nationalistic perspectives - Dewantara, Jagad Aditya; Budimansyah, Dasim; Darmawan, Cecep; Efriani, Efriani (Universitas Negeri Yogyakarta, 2024)
This article explains and provides an overview of what has been faced in border areas, as well as efforts that can be made to resolve dynamic problems in border areas. Especially people in the border areas in West Kalimantan, which borders directly with Malaysia. The problems that arise are very complex, especially in various fields, especially the issue of nationalism. This article will discuss matters related to dynamic problems in border areas. Of course, various types of individual models respond to the problems they have faced, whether it will make an individual's sense of nationalism stronger or perhaps it will fade their sense of nationalism. Towards the homeland, it was bearing in mind that the role of the Indonesian government is minimal in dealing with problems in border areas. Various factors result in the government's inability to deal with problems in border areas.